Analisis Efektivitas Penggunaan E-Form Dalam Rangka Meningkatkan Kepatuhan Wajib Pajak Badan Di KPP Jakarta Menteng Satu Tahun 2022-2023 - Supriyono, Supriyono; Lestari, Ayu Septi (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Initially the Tax Return (SPT) was submitted manually through the Tax Service Office, then along with developments in science and technology, the Directorate General of Taxes implemented an internet based tax service system namely, E-Form. This research aims to analyze the Effectiveness os Use E-Form In Order to Improve Corporate Taxpayer Compliance. The research method that the author uses in this research is a qualitative descriptive method with data collection techniques using interviews, observation, documentation and triangulation. The effectiveness theory used uses the Beni, Pekei theory. The results of the study concluded that the use E-Form it is quite effective in increasing taxpayer compliance but is not optimal because there are still obstacles in human resource factors and technological factors in carrying out work. Which hinders the effectiveness of use E-Form is that there are still taxpayers who do not understand E-Form, occurs server down or failed impor csv file. Efforts made to overcome these obstacles include being persuasive and providing comprehensive outreach and education to taxpayers regarding E-Form so that they can carry out their rights and obligations in accordance with applicable regulations.